2011
DOI: 10.1186/1756-0500-4-354
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective review to determine the utility of follow-up skeletal surveys in child abuse evaluations when the initial skeletal survey is normal

Abstract: ObjectiveThe AAP recommends that a follow-up skeletal survey be obtained for all children < 24 months of age who are strongly suspected to be victims of abuse. The objective of the current study was to evaluate the utility of a follow-up skeletal survey in suspected child physical abuse evaluations when the initial skeletal survey is normal.MethodsA retrospective review of radiology records from September 1, 1998 - January 31, 2007 was conducted. Suspected victims of child abuse who were < 24 months of age and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 7 publications
0
31
0
3
Order By: Relevance
“…109,116 The follow-up examination may identify fractures not seen on the initial skeletal survey, can clarify uncertain findings identified by the initial skeletal survey, and improves both sensitivity and specificity of the skeletal survey. 116,117 In one study, 13 of 19 fractures found on the follow-up examination were not seen on the initial series. 116 The number of images on the follow-up examination may be limited to 15 views by omitting the views of the skull, pelvis, and lateral spine.…”
Section: Imaging Approachmentioning
confidence: 99%
“…109,116 The follow-up examination may identify fractures not seen on the initial skeletal survey, can clarify uncertain findings identified by the initial skeletal survey, and improves both sensitivity and specificity of the skeletal survey. 116,117 In one study, 13 of 19 fractures found on the follow-up examination were not seen on the initial series. 116 The number of images on the follow-up examination may be limited to 15 views by omitting the views of the skull, pelvis, and lateral spine.…”
Section: Imaging Approachmentioning
confidence: 99%
“…[4][5][6][7][8][9]29 Although of different design, and occurring in different time periods (some involving screen-film and others computed or digital radiography), all have supported the utility of SS2 in the evaluation of child abuse. Our study also demonstrates this utility, and our yield of 38.8% is comparable to the yield demonstrated in previous studies (14%-61%).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have found that all children with normal initial surveys have normal follow-up surveys14 while others such as Bennett et al 16 found otherwise. They analysed the follow-up skeletal surveys of 47 children who had normal initial skeletal surveys and found signs of healing bone trauma in 8.5% (4/47); three children had healing rib fractures and one had a proximal humeral fracture.…”
Section: Follow-up Skeletal Surveysmentioning
confidence: 99%